Serological survey of mumps antibodies in adults in the Czech Republic and the need for changes to the vaccination strategy. Issue 4 (3rd April 2018) - Smetana, Jan; Chlibek, Roman; Hanovcova, Irena; Sosovickova, Renata; Smetanova, Libuse; Polcarova, Petra; Gal, Peter; Dite, Petr
ABSTRACT: Mumps outbreaks, especially in adolescents and young adults, have been reported in the Czech Republic. The aim of the presented study was to determine the seroprevalence of specific IgG antibodies against mumps in the adult population of the Czech Republic. The study was designed as a multicenter serological survey of adults aged 18 years and over. Specific IgG antibodies against mumps were detected in blood samples using an enzyme-linked immunosorbent assay (ELISA). A total of 1, 911 serum samples were examined. The overall seropositivity reached 55.3%. In individual age groups, the highest seropositivity 63% (63.5–65.2%) was recorded in adults aged 40 years and over; the lowest seropositivity was found in adults aged 18–29 years (27.4%). The difference in seropositivity rate between the 18–29 years age group and the 40 years and over age groups was statistically significant (p < 0.001). Only the 18–29 years age group included both vaccinated and unvaccinated (born in the pre-vaccine era) individuals. In vaccinated individuals, seropositivity was reported in only 19.1% of persons; in unvaccinated individuals, seropositivity reached 48.2%. Our results demonstrate the long-term persistence of antibodies following natural infection and the decrease in seropositivity that occurs after vaccination over time. This immunity waning may account for the higher susceptibility of adolescents and young adults to mumps. Therefore, the current vaccination program in the Czech Republic could be considered as less effective. It will be modified with the shifting of the second dose of vaccine from two years of age to the preschool age.